Rational points on intersections of cubic and quadric hypersurfaces - Browning, T; Dietmann, R; Heath-Brown, D (Cambridge University Press, 2015)
We investigate the Hasse principle for complete intersections cut out by a quadric hypersurface and a cubic hypersurface defined over the rational numbers.